Robots, Pirates, and the Rise of the Automated Takedown Regime: Using the DMCA to Fight Piracy and Protect End-Users - Carpou, Zoe (The Columbia Journal of Law & the Arts, 2016)
This very second, a battle between robots and pirates is being waged online. Pirates are stealing content from copyright holders and uploading it to various websites. Robots are crawling the Web, searching for pirated content. When a robot encounters pirated content, it is programmed to attack—either by reporting back to the copyright holder, or by going straight to the source and requesting that the material be removed. Sometimes the pirates fight back, re-posting the content online soon after it is taken down or posting newly infringing content. The cycle continues, and the battle rages on.